In-silico approach to design a novel multi-epitope vaccine against Zika Virus - Mardiya, Radiya Tum; Mahabub, Umaiya Binte (Brac University, 2024)
This thesis submitted to the Department of Mathematics and Natural Sciences in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2024.